The Effectiveness of Using Educational Games as an Educational Tool in Learning Akidah Akhlak at MTs. Al-Jam’yatul Washiliyah Medan - Nisah Nirawana Sinaga; Hasrian Rudi Setiawan (Universitas Muhammadiyah Enrekang, 2024)
This study aims to evaluate the effectiveness of using educational games as a learning tool in the subject of moral creed at MTs. Al-Jam'iyatul Washliyah Medan. Educational games are expected to be a more interesting alternative for students than conventional and monotonous methods. To achieve this goal, the research used a qualitative descriptive method based on the Miles and Huberman interactive analysis model, which consists of four main stages: data collection, data presentation, data reduction, and conclusion drawing or data verification. The data validity technique applied is triangulation, which is a verification process by combining various sources of information, methods, and perspectives to ensure that the data obtained has high validity and reliability. Data was collected through direct observation, interviews with teachers and students, and learning documentation. The results showed that using educational games in learning akidah akhlak proved to be quite effective in increasing students' learning motivation. Educational games provide a fun and interactive experience, so students are more excited and interested in learning the material of moral creed. In addition, this study also found that this approach can increase students' active involvement in the learning process and help them understand the concepts of moral creed in a more practical and applicable way.